Novel rare-earth and transition metal-based entropy stabilized oxides with spinel structure. (15th March 2020) - Parida, Tripta; Karati, Anirudha; Guruvidyathri, K.; Murty, B.S.; Markandeyulu, G.
Abstract: Entropy stabilization was attempted through the addition of 5 different rare earth cations, 5 different transition metal cations and all these 10 cations in the form of three compounds based on NiFe2 O4 . Equiatomic ratios of these cations were used to maximize the entropy stabilization effect. The compounds attempted and investigated were NiFe1.9 (Dy0.02 Er0.02 Gd0.02 Ho0.02 Tb0.02 )O4, (Co0.2 Cr0.2 Fe0.2 Mn0.2 Ni0.2 )Fe2 O4 and (Co0.2 Cr0.2 Fe0.2 Mn0.2 Ni0.2 )Fe1.9 (Dy0.02 Er0.02 Gd0.02 Ho0.02 Tb0.02 )O4 . Synthesis of these compounds were carried out by sol–gel technique and all the compounds were found to crystallize in F d 3 ¯ m spinel structure indicating the entropy stabilization. An appropriate calculation of configurational entropy of mixing employing the sublattice model is demonstrated for such entropy stabilized oxides. Graphical abstract: Image, graphical abstract